CLASS MANAGEMENT IN IMPROVING THE QUALITY OF ISLAMIC BOARDING SCHOOL EDUCATION - Khotimah, Khusnul; Suswati, Suswati; Muhajir, Muhajir; Wibowo, Adi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to describe the student management of MTs Negeri 1 Purworejo, the implementation of student programs in an effort to improve student achievement, and the implementation of student programs in an effort to shape student character at MTs Negeri 1 Purworejo. This type of research is descriptive qualitative. Data collection methods use observation, interviews and documentation methods. Data validity was carried out using data triangulation. The data analysis technique uses a flow model according to Miles and Huberman, namely data collection, data reduction, data presentation, and drawing conclusions. The research results show that: 1) Student management at MTs Negeri 1 Purworejo is carried out by planning, organizing, actualizing and supervising student programs in the field of student development. 2) Implementation of student programs in an effort to improve student achievement at MTs Negeri 1 Purworejo is carried out through fostering academic achievement by the curriculum sector, fostering non-academic achievement through extracurricular activities and building achievement. 3) Implementation of student programs in an effort to shape student character at MTs Negeri 1 Purworejo is carried out through firstly developing student discipline, secondly character building by integrating character values in learning tools, integrating character values in P5RA, self-development or habituation, exemplary activities, and nationalism activities and patriotism.Keywords: Manajemen Kesiswaan, Prestasi Siswa, Karakter Siswa.